United Arab Emirates 1975/76-2018 (Contemporary Archive of the Islamic World, 2019)
The second volume in a new series, the Contemporary Archive of the Islamic World (CAIW), this title draws on the resources of World of Information, a Cambridge-based British publisher that since 1975 has published analyses of the politics and economics of all the Middle East countries. The United Arab Emirates is a young country. This title covers the first four decades or so of the country's existence looking at the individual emirates, their rulers and their tribes. Rivalries occasionally became conflicts, but year by year differences have diminished and unity prevailed. In this title each annual overview gives a comprehensive picture.